What is medicine? : Western and Eastern approaches to healing - Unschuld, Paul U. (Paul Ulrich), 1943- (University of California Press, 2009)
A comparative history, this book looks at the different ways & contexts in which European and Chinese medicine have developed, arguing that each has been and remains as legitimate a path to follow as the other.